2021
DOI: 10.1038/s41598-020-79046-y
|View full text |Cite|
|
Sign up to set email alerts
|

Reconstructing hotspots of genetic diversity from glacial refugia and subsequent dispersal in Italian common toads (Bufo bufo)

Abstract: Genetic diversity feeds the evolutionary process and allows populations to adapt to environmental changes. However, we still lack a thorough understanding of why hotspots of genetic diversity are so 'hot'. Here, we analysed the relative contribution of bioclimatic stability and genetic admixture between divergent lineages in shaping spatial patterns of genetic diversity in the common toad Bufo bufo along the Italian peninsula. We combined population genetic, phylogeographic and species distribution modelling (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 78 publications
(134 reference statements)
4
20
0
Order By: Relevance
“…The BSPs detected demographic expansion within all three haplogroups (Figure 6); WcII and WcIII appear to have begun a Identifying hotspots of intraspecific diversity and areas of historical refugia is important for the conservation of imperilled taxa (Petit et al, 2003;Canestrelli et al, 2010;Chiocchio et al, 2021). Mussels in Mediterannean-climate regions are more imperilled and face a wider range of threats than other mussels globally, but the phylogeographical research effort on this group has not been equal among these regions (Benson et al, 2021).…”
Section: Demographic Historymentioning
confidence: 99%
See 2 more Smart Citations
“…The BSPs detected demographic expansion within all three haplogroups (Figure 6); WcII and WcIII appear to have begun a Identifying hotspots of intraspecific diversity and areas of historical refugia is important for the conservation of imperilled taxa (Petit et al, 2003;Canestrelli et al, 2010;Chiocchio et al, 2021). Mussels in Mediterannean-climate regions are more imperilled and face a wider range of threats than other mussels globally, but the phylogeographical research effort on this group has not been equal among these regions (Benson et al, 2021).…”
Section: Demographic Historymentioning
confidence: 99%
“…Traditionally, this process has been described as a contraction to major refugia, where a panmictic, stable and genetically diverse population is maintained (Hewitt, 2000). More recently, numerous authors have shown that the process may actually involve ‘refugia‐within‐refugia’, whereby multiple isolated populations persist within the broader refugial area (Byrne, 2008; Canestrelli et al, 2010; Canestrelli et al, 2014; Chiocchio et al, 2021). In this scenario, hotspots are ‘melting pots’ generated by (a) localized contraction and divergence of these populations and (b) subsequent admixture during re‐expansion (Canestrelli et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two endemic Bufo species on the Japanese mainland, Bufo japonicus Temminck and Schlegel, 1838 and B. torrenticola Matsui, 1976 ( Matsui & Maeda, 2018 ). Although the effects of the Quaternary climate on European toads have been examined in detail ( e.g ., Garcia-Porta et al, 2012 ; Arntzen et al, 2018 ; Chiocchio et al, 2021 ), limited information is currently available on B. japonicus and B. torrenticola . Bufo japonicus is widely distributed in Honshu, Shikoku, Kyushu, and some adjacent islands and is a lentic breeder, similar to the majority of congeneric species.…”
Section: Introductionmentioning
confidence: 99%
“…During periods of unsuitable climatic conditions, species’ ranges contracted into climatic refugia, whereas range expansions followed the re-establishment of suitable conditions (Hewitt, 1996; 2000; 2011a; Weiss & Ferrand, 2007). The legacies of range dynamics on species genetic structures have been widely investigated during the last decades (Hewitt, 2000; Avise, 2009; Hewitt, 2011b; Lucati et al, 2020; Chiocchio et al, 2021), whereas evidence on their role in moulding intra-specific phenotypic variation is scarce. Yet, phenotypic traits are likely to vary in response to dispersal processes, especially during range expansions (Canestrelli et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%